Proposed Business Strategy for Travel Agency Company to Face the New Normal (Case Study: Tazakka Tour and Travel) (The Indonesian Journal of Business Administration, 2020)
Pandemic Covid-19 demanded all of the business activities around the world to adapt quickly in the uncertain situation and condition. Tazakka Tour and Travel run business with having cooperation with few companies and also sell it their service to customers in directly. In this research, the company want to make a new business strategy in order to survive in the travel business sector.Researcher use SWOT Analysis to measure the strength, weakness, opportunity, and threat that will come to the company from the external (PESTEL Analysis, Five Porter’s Forces, and Marketing Mix). Furthermore, from the internal (Business Model Canvas, STP, and also VRIO Analysis) that has been done before.Moreover, the company need to make Digital Integrated Marketing Communication as for sustainable development of the company. Not only that, the company also need to make short-term, mid-term, and long-term target for the next few years.Lastly, after the analysis has done by determining the literature of Tazakka Tour and Travel and the resolution of the literature by using SWOT-TOWS matrix, also applicate technological approach with smart apps on consumer renewable services. Keywords: Covid-19, Tour and Travel, New Normal, SWOT-TOWS Analysis, Marketing Mix 7P, Integrated System